PROFESSIONAL VALUES IN YOUTH EDUCATION - Lidaka, Anita; Priedolina, Madara (European Scientific Journal, ESJ, 2014)
Human factor plays an important role in sustainable development of a state without which the planned changes would not be possible. It determines the importance of preparing future specialists. Education acquired by students lays the basis for strengthening future welfare. Higher education institutions are in charge of implementation of different study programmes by carrying out the established aims and objectives. Improvement of the study course content ensures preparing good and competitive specialists. Often, problems arise due to students’ poor awareness of the profession, the potential field of activity, the necessary knowledge, skills and attitudes Internal and external motivation is the influential strength, which makes the process of learning a profession more focused. A successful career relates to an appropriate career choice in line with the interests and abilities. In order for today’s students to successfully join the labour market, acquiring values important for the profession must be included in the educational process.